Impacto do extrato da casca de café (Coffea arabica L.) nos processos oxidativos em hambúrguer de frango - Marques, Antonia Dayane Jenyffer de Farias (2022)
Oxidation reactions are a series of chemical changes that adversely affect food quality and are considered one of the main factors in the spoilage of meat and meat products. Coffee husks, a residue from coffee processing, contain highly desirable chemical substances, especially phenolic compounds, which are secondary metabolites known for their antioxidant properties that can prevent and control oxidative reactions. The aim of this study was to evaluate the antioxidant capacity of coffee husk extract (Coffea arabica L.) added to chicken hamburger. Two formulations with addition of the extract (100 and 200 ppm CAE/kg) were prepared, besides the control formulations without addition of antioxidants and with addition of synthetic antioxidants. The products were characterized by physical and chemical analyzes and tested for oxidative stability at 15-day intervals during 45-day storage under freezing conditions. The addition of the extract containing 200 ppm CAE/kg hamburger showed equivalent efficacy to the treatment with synthetic antioxidant against lipid oxidation. As for protein oxidation, there was no effect of pro- or antioxidant in the treatments. The addition of organic coffee husk extract in chicken hamburger is indicated and therefore considered as a potential natural additive. In addition, the use of coffee husks helps to minimize the amount of agro-industrial by-products generated in the coffee industry and adds value to the product.